College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.6 - Transformations of Functions - 2.6 Exercises: 68

Answer

$g(x)=-(x-2)^2+1=-x^{2}+4x-3$

Work Step by Step

We obtain $g(x)$ by reflecting $f(x)=x^2$ about the $x$-axis and shifting right 2 units and up 1 unit, i.e. $y=-f(x-2)+1$ $g(x)=-(x-2)^2+1=-(x^2-4x+4)+1=-x^{2}+4x-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.